Pengelolaan Kader dan Warga dalam Edukasi Pencegahan Tatalaksana Awal Infeksi Saluran Pernapasan Akut pada Anak di Puspasari Bogor - Warini, Warini; Sartika, Sartika; Raharsari, Razeki Tri; Amailia , Sisi; Fauzia, Nura Suciati; Istiqomatunnisa, Istiqomatunnisa; Firmansyah, Firmansyah (Yayasan Inspirasi El Burhani, 2024)
Abstract Introduction: Acute Respiratory Infection (ARI) is a disease caused by viruses or bacteria that is usually transmitted depending on the causative pathogen, environmental factors, and the consequences of the mortality and morbidity rates in developing countries are quite high and Acute Respiratory Infection (ARI) is one of the causes of the high prevalence of morbidity in toddlers. The immune system of children under 5 years of age that is formed is still not strong enough so that it can increase the risk of ARI. Objective: Educating cadres and the community about the prevention and early management of respiratory tract infections in children at Puspasari Bogor with 55 participants consisting of 32 mothers with children aged 5 months - 5 years and 12 health cadres. Method: Community service on early management and prevention of ARI targeting mothers with toddlers was carried out on August 30 - September 8, 2024, carried out in 3 stages with stage 1 determining health problems. second determining interventions and implementing and third evaluation at the Citeurep Health Center and Mawar Posyandu. Education or counseling was carried out by lecturers from the Annisa Health and Business Institute, Diploma III Midwifery Study Program, Diploma III Nursing, Bachelor of Hospital Administration accompanied by the distribution of leaflets to mothers. The knowledge of mothers is very important in the future, so pretests and posttests were carried out related to the material presented. Result: Evaluation of the activity program by distributing pre- and post-test questionnaires, where there was an increase in the percentage of understanding of prevention of early management of acute respiratory infections in residents by an increase of 36% Both stated from the pretest 44% to the Posttest 80% This shows a good number. Conclusion: Based on the results of the evaluation of Community Service activities, the knowledge of cadres and mothers with toddlers has increased significantly. Although ARI is a disease that is considered common, it has an impact if not treated immediately. The need for family support and health facilities in responding to it. Keywords: Acute Respiratory Tract Infection, Education of health cadres and mothers with toddlers